Myosin-X: A molecular motor driving cancer cell invasion - Miihkinen, Mitro (fi=Turun yliopisto|en=University of Turku|, 2016)
In metastasis migratory cancer cells invade through stroma and spread throughout the body forming metastatic colonies into distant organs. Myosin-X is a member of the vast myosin superfamily of actin dependent motor proteins. Functionally very different from myosin-II, myosin-X works by transporting intracellular cargo along actin filaments. Myosin-X is able to induce filopodia formation and can support their function by transporting cargo towards filopodia tips. Among the myosin-X cargo are the integrin family of transmembrane receptors that have been for long known to be crucial for cell motility. Whereas integrins have roots in many aspects of migratory processes, myosin-X expression has been shown to worsen patient prognosis and increase metastatic potential. By using standard and novel cytometric techniques, state-of-the-art microscopy techniques and biochemical tools this Pro gradu thesis addresses how myosin-X (MYO10) supports filopodia-linked cancer cell invasion that is detected in single and collective cell migration. Myosin-X expression was found to inhibit 51 integrin activation via its FERM domain in triple-negative breast carcinoma and osteosarcoma cell lines. In addition, myosin-X expression was seemed to support integrin trafficking in a p53 mutant cell line but not in p53 wild-types cells. Upon PH domain disruption, myosin-X was found to localize to subcellular compartments and to the cell periphery together with 1 integrin. In this case myosin-X was unable to inactivate 1 integrin, perhaps due to loss of a direct interaction. However, PH domain deficient myosin-X lowers total 1 integrin levels at the plasma membrane. In total, data from experiments on myosin-X with disrupted or missing PH domain suggest a common route of trafficking for these proteins. Structural bioinformatics, proximity ligation assay and a novel proteoliposomal binding assay were used to further assess the interaction between myosin-X and integrin. In the process, a previously unnoticed RA-like subdomain was discovered to be situated inside myosin-X FERM domain.